Long-range prediction of the tropical cyclone frequency landfalling in China using thermocline temperature anomalies at different longitudes - Liu, Chunlei; Zheng, Rong; Jin, Liang; Bao, Ruijuan; Cao, Ning; Liao, Xiaoqing; Xue, Yufeng; Chen, Hailiang; Yang, Ke; Su, Qianye (Frontiers in Earth Science, 2023)
The landfalls of the tropical cyclone (TC) along the coast of China have caused huge damages economically. There are about nine TC landfalls in China every year. It will be helpful if the landfall frequency can be predicted in advance. Inspired by the study of Sparks and Toumi (2020), six datasets, including four ocean reanalyses and two object analyses from 1993-2019, are employed to study the consistency in the relationship between the thermocline temperature anomalies at different longitudes and the frequency of TC landfalls along coastal areas of China (South China, East China and the whole China). The thermocline temperature anomalies at different longitudes are tested in order to confirm our hypothesis that the eastward and westward transports of ocean heat from the warm pool are causes of the significant correlations. Results show some significant correlations at various longitudes and the temperature anomalies can lead the TC landfall frequency several months or longer. Further study also shows the close relationship between the ocean heat transport and the sea surface temperature anomalies at the genesis locations of landfall TCs. The locations of the Western Pacific Subtropical High (WPSH) during high-frequency TC landfall years also show favorable spatial patterns to the TC landfall in South China and East China, respectively. In years with high TC frequency in South China, the westward displacement of the WPSH ridge steers the TC towards South China. While during high-frequency TC landfall years in East China, the WPSH is located further north, and the westward extension of the ridge is in close proximity to East China Sea.